PENGARUH PENGHARGAAN DAN KOMITMEN TERHADAP KINERJA GURU TK SWASTA KABUPATEN SINTANG KALIMANTAN BARAT - Yuniarti . (Universitas Muhammadiyah Ponorogo, 2017)
The objective of this research was to understand the effect of rewards nd commitment on performance. Quantitative researc has conducted in fifteenkindergarten located in SintangRegency, West Kalimantan. The research uses a survey method with path analysis was applied in testing hypothesis. It was conducted to 80 teachers at Kindergarten School as the respondents which were selected in a simple random way. The result of this study are : (1). There is a positive direct effect of rewards on performance. (2). There is a positive direct effect of commitment on performance, and (3). There is a positive direct effect of rewards on commitment